Un site urbain façonné par l’industrie : Thiers, ville coutelière - Anne Henry (In Situ)
The evolution of the town of Thiers is strongly marked by the intense industrial activity of the locality, specialised in cutlery production for nearly seven centuries. This impact of industry is particularly visible in the Durolle gorge, where there are nearly forty factories and workshops. The presence of industry is also perceptible in the historic centre of the town, where drying sheds for paper and cutlery workers’ shops are integrated into the medieval habitat. The technical advances which marked the industry during the nineteenth and twentieth centuries also had a notable influence on the evolution of the town and its factories. The development of means of communication, the mechanisation of production processes and electrification all contributed to an unprecedented growth of cutlery production and of the town as a whole.